Implementation of Economic Cooperation Program (ECP) Under Indonesia Australia - Comprehensive Economic Partnership Agreement (IA-CEPA) - Ramdlani, Muhammad Riyan Fitria; Rohmah, Neneng Sobibatu; Pambudi, Dimas Purbo (Public Policy and Management Inquiry, 2025)
This research presents a critical review by analyzing and evaluating the implementation of the ratification of the Indonesia-Australia relationship based on the IA-CEPA. Therefore, the focus of this research question is how the implementation and effectiveness of the ‘economic powerhouse’ in the IA-CEPA. The concept of public policy guides this study to analyze the results of the implementation of the IA-CEPA cooperation between Indonesia and Australia. To answer the research question, this article uses a qualitative research method through a literature study to analyze the implementation of the IA-CEPA. The results of this study indicate that IA CEPA serves as a bridge of mutualism to advance the interests of both nations, especially in the economic sector for the welfare of the people. Through reciprocal skills exchange programs, on-the-job training, and regulations governing work and holiday visas, IA-CEPA has succeeded in improving the capabilities and knowledge of the Indonesian workforce in the field of human resource development.